Emotional Intelligence in Children with Severe Sleep-Related Breathing Disorders. (5th September 2019) - Operto, Francesca Felicia; Precenzano, Francesco; Bitetti, Ilaria; Lanzara, Valentina; Fontana, Maria Lorena; Pastorino, Grazia Maria Giovanna; Carotenuto, Marco; Pisani, Francesco; Polito, Anna Nunzia; Smirni, Daniela; Roccella, Michele
Abstract : Background . Obstructive sleep apnea syndrome (OSAS) affects up to 4% of a pediatric population, with many comorbidities in the medium-long term. Functional alterations in the prefrontal cortex (PFC) may explain why OSAS impacts aspects such as executive functions, memory, motor control, attention, visual-spatial skills, learning, and mood regulation. Emotional intelligence (EI) is a complex neuropsychological function that could be impaired in many clinical conditions. Purpose . The aim of the study is to evaluate the difference in emotional intelligence skills among children with OSAS and healthy subjects (nOSAS). Methods . 129 children (72 males; mean age7.64 ± 1.98 years) affected by OSAS were compared to 264 non-OSAS (nOSAS) children (138 males; mean age7.98 ± 2.13 ) similar for gender, age, and socioeconomic status. In order to assess the emotional quotient, the Bar-On Emotional Quotient Inventory: Youth Version (EQ-i:YV) was used. Results . The comparison for means and standard deviation between OSAS children and nOSAS children for EQ-i:YV scores showed significant differences for Interpersonal, Adaptability, and Stress Management scales and EQ Total score. Conclusions . Our findings highlighted the role of intermittent hypoxia in the genesis of the effects of sleep-related respiratory disorders, which involves also aspects different from physical impairments.